Strategic formulation to increase white tea competitiveness (Case study: Research Institute for Tea and Cinchona) - Hage, Stevan Gneissanda; Daryanto, Arief; Sahara, Sahara (Jurnal Penelitian Teh dan Kina, 2015)
White tea is a new product in Indonesiaâs tea industry. It is a product developed by Research Institute for Tea and Cinchona in order to revive Indonesiaâs tea industry. White tea has uniqueness in its relatively high price and high market demand that not affected by its high price. The increasing number from Indonesiaâs middle class income could also become white teaâs new potential consumer because they put quality and health first than the price. White teaâs high price and demand attract new players in this industry. The appearence of new competitors make this in-dustry more competitive. Thatâs why itâs necce-sary to find a way to win the compettion and to keep the domination in the white tea industry through strategic formulation. There were two steps in strategic formulation used to produce the strategies. The first is analyzing the com-pany environment using internal factor evalua-tion (IFE) and external factor evaluation (EFE). The second is using internal and exter-nal (IE) matrix and strength weakness oppor-tunity and threat (SWOT) analysis. IE matrix showed the position of company using infor-mation from IFE and EFE. SWOT analysis resulted strategies using information from the companyâs strength, weakness, opportunity, and threat. IFE and EFE showed that the company has strong internal power and good respond to external factors. IE matrix showed that com-pany is in grow and build stage. IE matrix and SWOT analysis showed that the alternative strategies for the company are market pene-tration, market development, product develop-ment, forward integration, backward integ-ration, and side integration.